2016
DOI: 10.1089/bio.2015.0104
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Isolation Techniques for Human Peripheral Blood Mononuclear Cells: Cell Recovery and Viability, Population Composition, and Cell Functionality

Abstract: Routine techniques for the isolation of human peripheral blood mononuclear cells (PBMCs) include density centrifugation with Ficoll-Paque and isolation by cell preparation tubes (CPTs) and SepMate tubes with Lymphoprep. In a series of experiments, these three PBMC isolation techniques were compared for cell recovery and viability, PBMC population composition, and cell functionality, aiming to provide a starting basis for the selection of the most appropriate method of PBMC isolation for a specific downstream a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 11 publications
2
85
0
Order By: Relevance
“…For MB, there are no differences between blood sample lots regarding platelet contamination while for ST, the 1ml lot was significantly less contaminated than its 2ml and 3ml counterparts. Regarding cell recovery, our results are consistent with previous studies reporting an average cell recovery by Ficoll isolation between 0.6 and 3 million cells per ml of blood [19][20][21][22]. However, we consider that when assessing performance, "cells per ml of blood" is an inappropriate manner of reporting cell recovery since it provides no information about initial cell count and cell population composition.…”
Section: Pbmc Recovery Purity Viability and Platelet Contaminationsupporting
confidence: 87%
“…For MB, there are no differences between blood sample lots regarding platelet contamination while for ST, the 1ml lot was significantly less contaminated than its 2ml and 3ml counterparts. Regarding cell recovery, our results are consistent with previous studies reporting an average cell recovery by Ficoll isolation between 0.6 and 3 million cells per ml of blood [19][20][21][22]. However, we consider that when assessing performance, "cells per ml of blood" is an inappropriate manner of reporting cell recovery since it provides no information about initial cell count and cell population composition.…”
Section: Pbmc Recovery Purity Viability and Platelet Contaminationsupporting
confidence: 87%
“…Another study found the overall performance of PBMCs isolated with CPTs and SepMate Tubes (comparable to LP tubes) to be similar, but superior than those isolated using Ficoll-Paque alone [15]. For example, in that study, cells isolated with either CPT or SepMate resulted in a greater number of PBMCs and higher IFNγ expression after staphylococcal enterotoxin B (SEB) stimulation than PBMCs isolated using only Ficoll-Paque gradient [15].…”
Section: Discussionmentioning
confidence: 94%
“…Calcium and magnesium free PBS, pH7.2, (Invitrogen, Pty Ltd. Australia) was used after adding 2 mM EDTA and 2% heat-inactivated fetal bovine serum (FBS) (Invitrogen, Pty Ltd. Australia); PBS buffer. SEPMATE tubes (50 ml) with inner inserts (STEMCELL technology, Canada) were used to isolate PBMC following Ficoll-Paque density gradient protocol [29,30]. PBMCs were washed, counted and the required number of PBMC were co-cultured with S. thermophilus 285 and the remaining PBMC were stored in freeze mix and transferred into liquid nitrogen for future use.…”
Section: Isolation Culture and Stimulation Of Pbmcmentioning
confidence: 99%